Perceptions of air quality and concern for health in relation to long-term air pollution exposure, bushfires, and COVID-19 lockdown: A before-and-after study - Alec T. Cobbold; Melanie A. Crane; Luke D. Knibbs; Ivan C. Hanigan; Stephen P. Greaves; Chris E. Rissel (Elsevier, 2022)
Background: Air pollution is a major health burden and the leading environmental risk factor for non-communicable diseases worldwide. People's perceptions and concerns about air pollution are important as they may predict protective behaviour or support for climate change mitigation policies. Methods: This repeat cross-sectional study uses survey data collected from participants in Sydney, Australia in September-November 2019 (n = 1,647) and October-December 2020 (n = 1,458), before and after the devastating 2019/2020 bushfires and first COVID-19 lockdown restrictions in Sydney in 2020. Participants' perceptions of air quality and concerns for health in relation to air quality were modeled against estimates of annual average NO2 and PM2.5 concentrations in their neighbourhood. Results: Participants in suburbs with higher estimated air pollution concentrations generally perceived poorer air quality and were more concerned for health in relation to air quality. A 5 µg/m3 increase in NO2 was associated with perceived poorer air quality (OR 1.32, 95%CI 1.18-1.47). A 1 µg/m3 increase in estimated PM2.5 was associated with perceived poorer air quality (OR 1.37, 95%CI 1.24-1.52) and greater concern for health (OR 1.18, 95%CI 1.05-1.32). Air quality was perceived as better in 2020 than in 2019 in both NO2 and PM2.5 models (p<0.001). Air quality concern increased in 2020 in both models. Discussion: This study provides the first Australian data on the association between estimated air quality exposure and air quality perceptions and concerns, contributing new evidence to inform public health approaches that increase awareness for air pollution and reduce the health burden.